Evaluation of Forces Resulting from Premature Occlusal Contact Between First Molars: A 3D Finite Element Study (Research, Society and Development, 2021)
Occlusal contacts are considered important factors to be considered before dental treatment, as premature occlusal contacts can cause potential damage to oral health. The biomechanical events that result from premature occlusal contacts on teeth and their supporting tissues remain unclear. Thus, the purpose of this study was to evaluate, using the three-dimensional finite element method, the distribution of stresses, in teeth and supporting tissues, generated by different premature contacts in upper and lower first molars. The research was designed considering two factors of premature contacts that are possible to occur clinically, “A” contact and “B” contact. Meshes were generated using the Solidworks® software and the tests were performed using the Cosmos Design Star finite element software, with a load intensity of 100 N on the occlusal face. Von Mises maps were generated for stress distribution analysis. Higher stresses were generated by premature “A” contact. Premature contact points in first molars generated large concentrations of stresses in the centric cusps, and in the upper first molars, depending on the type of contact, the stresses can dissipate towards the apex of the root. Stresses are better dissipated in the support fabric of the upper hemi-arch.